PENGARUH KREDIBILITAS USTADZ ABDUL SOMAD TERHADAP KEPUTUSAN JAMA’AH UNTUK MENGIKUTI KEGIATAN DAKWAHNYA DI PEKANBARU - Ade Nur Ashfiah; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The Information is something that is important for humans because it can help meet their needs. communicator as a source of information must be able to account for the validity of the message conveyed by mastering and understanding the message. Sources with high credibility also have a higher influence in influencing the audience. So the research in this thesis is to answer how much influence Ustadz Abdul Somad has had on the decision of pilgrims to take part in his missionary activities in Pekanbaru.          The study uses quantitative explanatory methods using unknown population techniques with a sample of 166 respondents. Researchers collected data with questionnaires. To find out how much influence between the independent and dependent variables. Researchers use simple linear regression analysis. Data processing of the questionnaire test was carried out using Windows Version 23 SPSS program.   Based on the equation Y = -0.783 + 1,027X + e constant (a) of -0.783. This means that if the credibility of Ustadz Abdul Somad is assumed to be zero (0), then the decision of pilgrims to take part in preaching activities in Pekanbaru is worth -0,783. The regression coefficient value of 1.027 states that if the credibility of Ustadz Abdul Somad has increased by 1 unit, then the decision of pilgrims to take part in preaching activities in Pekanbaru will increase by 1,027 points. This means that the influence of Ustadz Abdul Somad's credibility of 96.5% on the decision of pilgrims to take part in preaching activities in Pekanbaru has a very strong influence.Keywords: Source credibility Theory, Ustadz Abdul Somad, decision-making